Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1021/jp055188t
|View full text |Cite
|
Sign up to set email alerts
|

Local Aromaticity of the Lowest-Lying Singlet States of [n]Acenes (n = 6−9)

Abstract: The local aromaticities of the six-membered rings in the two lowest-lying singlet states of [n]acenes (n = 6-9) have been assessed by means of three probes of local aromaticity based on structural, magnetic, and electron delocalization properties. Important differences between the local aromaticities of the closed-shell and diradical singlet electronic states are found. Thus, while the inner rings have the largest aromatic character in the closed-shell singlet states, the outer rings become the most aromatic f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
64
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(79 citation statements)
references
References 31 publications
(35 reference statements)
14
64
1
Order By: Relevance
“…Diradical singlet state of 2,3-anthraquinone and its larger analogues (n ≥ 3, n being the number of the rings), obtained using the unrestricted broken symmetry UB3LYP/6-311+G(d) method, is found to be more stable than the closed-shell singlet state; the energy differences amount to 5.2, 15.9, 12.1, and 10.2 kcal/mol for 2,3-anthra-, tetra-, penta-, and hexaquinones, respectively. This is similar to what is found for acenes [61], although in these latter cases, the closedshell species are more stable until n < 5 or 6. The change in the electronic ground state can also be understood using the Clar's π-sextet model [62].…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Diradical singlet state of 2,3-anthraquinone and its larger analogues (n ≥ 3, n being the number of the rings), obtained using the unrestricted broken symmetry UB3LYP/6-311+G(d) method, is found to be more stable than the closed-shell singlet state; the energy differences amount to 5.2, 15.9, 12.1, and 10.2 kcal/mol for 2,3-anthra-, tetra-, penta-, and hexaquinones, respectively. This is similar to what is found for acenes [61], although in these latter cases, the closedshell species are more stable until n < 5 or 6. The change in the electronic ground state can also be understood using the Clar's π-sextet model [62].…”
Section: Resultssupporting
confidence: 88%
“…It was recently shown that the lowest energy state of higher polyacenes can correspond to diradical singlet state instead of the closed-shell singlet state [59][60][61]. Similar results are also observed for some studied quinones.…”
Section: Resultssupporting
confidence: 77%
See 1 more Smart Citation
“…Indeed, this hexagonal nano-flake has attracted great interest with respect to its interesting properties like electronic absorption spectra, 119 and it has been successfully applied for modeling graphene in previous theoretical work. [120][121][122][123][124] Several theoretical studies have focussed on acenes [125][126][127] and oligoacenes [128][129][130][131][132] using DFT and ab-initio methods. However, because of the polyradical character of oligoacenes, 125,126 the spin ground state of these molecules have to be checked.…”
Section: Graphene Modelmentioning
confidence: 99%
“…[120][121][122][123][124] Several theoretical studies have focussed on acenes [125][126][127] and oligoacenes [128][129][130][131][132] using DFT and ab-initio methods. However, because of the polyradical character of oligoacenes, 125,126 the spin ground state of these molecules have to be checked. Singlet-triplet (S-T) excitation energies give valu- 137 The first S-S and S-T excitation energies were calculated to 1.94 and 1.77 eV, respectively.…”
Section: Graphene Modelmentioning
confidence: 99%